Pendampingan Implementasi Kurikulum Merdeka pada Pembelajaran IPA - PRELIA DWI AMANAH (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2026)
This community service program aims to enhance teachers’ understanding and capacity in implementing the Merdeka Curriculum in Natural Science (IPA) learning at the junior high school level. The program was conducted through mentoring, training, and reflective activities on curriculum implementation at a partner school, namely SMPN 6 Mataram. The service activities employed a participatory approach consisting of several stages, including needs analysis, curriculum training, assistance in developing teaching modules, classroom implementation, and program evaluation. The results of the program indicate that teachers gained a more comprehensive understanding of the concept of the Merdeka Curriculum, the development of teaching modules, the application of project-based learning, and the implementation of formative and summative assessments. Furthermore, teachers were able to integrate the values of the Pancasila Student Profile into science learning through experimental activities, group discussions, and simple scientific projects. The mentoring activities also had a positive impact on enhancing teachers’ creativity in designing learning processes that are more contextual, flexible, and student-centered. This community service program is expected to serve as a model for strengthening the implementation of the Merdeka Curriculum in schools and to promote the improvement of science learning quality that is more innovative and relevant to the demands of the 21st century.